2011
DOI: 10.1208/s12249-011-9608-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Vitro/In Vivo Evaluation of Etodolac Controlled Porosity Osmotic Pump Tablets

Abstract: Abstract. The aim of the current work was the design and evaluation of etodolac controlled porosity osmotic pump (CPOP) tablets exhibiting zero-order release kinetics. Variables influencing the design of (1) core tablets viz., (a) osmogent type (sodium chloride, potassium chloride, mannitol, and fructose) and (b) drug/osmogent ratio (1:0.25, 1:0.50, and 1:0.75), and (2) CPOP tablets viz., (a) coating solution composition, (b) weight gain percentage (1-5%, w/w), and (c) pore former concentration (5%, 10%, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The values of difference factor and similarity factor indicate that there was no significant difference between drug release profiles at different pH conditions as well as at different agitation intensities. In CPOP systems, pH and agitation intensity do not have any role in release mechanism of drugs (37). The physical observation of CPOP after completion of drug release study showed that increase in size of the tablet due to osmotic pressure leads to inflow of dissolution medium though the semipermeable membrane.…”
Section: Discussionmentioning
confidence: 98%
“…The values of difference factor and similarity factor indicate that there was no significant difference between drug release profiles at different pH conditions as well as at different agitation intensities. In CPOP systems, pH and agitation intensity do not have any role in release mechanism of drugs (37). The physical observation of CPOP after completion of drug release study showed that increase in size of the tablet due to osmotic pressure leads to inflow of dissolution medium though the semipermeable membrane.…”
Section: Discussionmentioning
confidence: 98%
“…The estimated pharmacokinetics parameters included; C max (the maximum drug concentration; ng/mL), t max (the time to reach C max ; h), MRT 0-∞ (the mean residence time, h), AUC (0-48h) (the area under the plasma concentration -time curve from zero to 48 h; ng h/mL) and AUC (0-∞) (the area under the curve from zero to infinity; ng h/mL) 30 . The relative bioavailability was calculated by dividing AUC (0-48h) of F6 over AUC (0-48h) of Benicar ® tablets.…”
Section: Pharmacokinetic and Statistical Analysesmentioning
confidence: 99%
“…For drugs that are administered orally, dissolution and intestinal permeation are considered as the rate-limiting steps for the absorption. Therefore, if an excellent correlation exists between in vitro dissolution test and a bioavailability parameter, then controlling the dissolution profile will permit the evaluation of bioavailability [57][58][59].…”
Section: In Vitro In Vivo Correlation (Ivivc) For Lipid Nanoformulationsmentioning
confidence: 99%